Grimm's fairy tales. - Grimm, Wilhelm 1786-1859.; Grimm, Jacob 1785-1863. (Bridlington, England P. Haddock)
A collection of forty-five favorite fairy tales from the Brothers Grimm, including "The Golden Bird," "Travelling Musicians," "Old Sultan", "The Frog Prince," "Ashenputtel," and "The Elves and the Shoemanke."
Keywords: Fairy tales -- Germany; Fairy tales; Folklore -- Germany